Characterization of the caruncular fusion in gestations of natural and cloned bovine conceptuses - da Silva Nunes Barreto, Rodrigo [UNESP]; Miglino, Maria Angélica; Meirelles, Flávio Vieira; Visintin, José Antônio; da Silva, Silmara Marcolino [UNESP]; Burioli, Kelen Cristina [UNESP]; da Fonseca, Ricardo [UNESP]; Bertan, Cláudia [UNESP]; de Assis Neto, Antonio Chaves [UNESP]; Pereira, Flávia Thomaz Verechia [UNESP] (FapUNIFESP (SciELO), 2009)
The objective of the study was to compare the characteristics of the caruncular fusion in gestations of non-cloned and cloned conceptuses. The non-cloned conceptuses were divided according to the gestation period: Group I (2 to 3 months; n=9), II (4 to 6; n=9); III (7 to 8; n=10) and IV (9 n=7). The cloned conceptuses formed the Group V: 9 months; n=4. The caruncles were observed macroscopically (number and dimensions: length, width and height), microscopically and submitted to statistical analysis (5% of significance). We observed three types of macroscopic caruncular fusions: oval (morphologically normal); two united adjacent caruncles and the lobulated type, characterized by regions with several united caruncles presenting a false fusion or deformation of the caruncular parenchyma. The length of the caruncles was 1.55±0.57; 2.45±0.55; 4.66±2.0 and 5.72±1.90cm for the groups I, II, III, IV respectively. As for the height, the caruncles presented a lineal growth during the gestation: 0.40±0.15; 0.57±0.21; 1.0±0.48 and 1.80±0.91cm, for the respective groups I, II, III and IV. The width of the caruncles was similar between the groups I and II (0.97±0.30 e 1.42±0.71cm) and the groups III and IV (2.68±1.22 and 3.52±1.16cm). When the group V was compared to the IV, the caruncles of the group V presented a larger length (5.72±1.90 vs. 7.88±.13cm) and width (3.52±1.16 vs. 4.93±1.46cm), however they were similar in height (1.80±0.91 and 2.25±0.67cm). We verified that in gestations of cloned conceptuses the caruncles presented a larger development than in gestations of non-cloned conceptuses. The fusioned caruncles presented measurements statistically similar to the isolated ones in all the parameters and groups. Under light microscopy, we observed the formation of a stromal axis from the basis of the caruncle to the apex of the fusional fissure, with the histological constitution similar to the endometrial stroma. Three microscopic shapes were also unpublished defined: true fusion with a single axis evident below the fusional fissure; pseudofusion with a double axis in H shape and false fusion with absence of the axis. The first two formats were associated to the oval and lobulated caruncles and the last one to the false fusion with deformation of the caruncle parenchyma. The fusional axis increased in size along the gestation among the groups I, II, III and IV. The group V presented a larger length and width of the axis when compared to the group IV. Thus, in gestations of cloned conceptuses a destruction of the lateral epithelium of the caruncles is associated to an incompetence in the maternal-fetal interdigitation, that compromises the cotyledonary fusion. We suggest that, in gestations derived of cloned conceptuses, the increase of the size of the caruncular fusions is possibly associated to a compensatory mechanism for the metabolic exchanges between mother and fetus, in reason of the smallest number of isolated caruncles.
Caracterização da fusão caruncular em gestações naturais e de conceptos bovinos clonados
Keywords: Caruncular fusion; Cloned cattle; Gestation